Emulador de cargas mecânicas com freio eletromagnético para ensaios de motores elétricos de indução - Mori, Marcio Massao Nishide (2018)
This work presents a load emulator coupled to an electromagnetic brake that enables the simulation of the main mechanical loads used by the industry. Allowing to evaluate the performance of motors of up to 10cv in applications with constant loads types, linear, parabolic and hyperbolic. The Mechanical Load Emulator consists of a dynamic information and graphing system, controlled by a user-friendly parameterized interface, executed on two platforms (Raspberry Pir II and Arduinor Uno), which during the motor tests coordinates the acquisition and display of data such as voltage, current, power, speed, temperature and torque.